The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/ijshe-03-2018-0048
|View full text |Cite
|
Sign up to set email alerts
|

Developing in engineering students a critical analysis about sustainability in productive systems

Abstract: Purpose The Mechanical Engineering course at the University of Campinas is composed of different disciplines in the areas of materials, mechanical design, manufacturing (production and manufacturing), computational systems, thermal and fluids. In the manufacturing area, in particular, there is a discipline entitled Productive Systems whose main objective is to offer to the student a global vision about operations management. In the field of operations management, sustainability is gaining more and more importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…As a consequence of it, analyzing the results of this study, it is clear that students from the sample must be better prepared better in relation to social aspects of sustainability, especially the concerns regarding employees and local communities. This is particularly important when it is considered the role of engineers in the development and improvement of production systems (Rampasso et al, 2018b). Another issue relevant to be addressed is the fact that maybe the environmental sustainability has not been emphasized enough in engineering courses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence of it, analyzing the results of this study, it is clear that students from the sample must be better prepared better in relation to social aspects of sustainability, especially the concerns regarding employees and local communities. This is particularly important when it is considered the role of engineers in the development and improvement of production systems (Rampasso et al, 2018b). Another issue relevant to be addressed is the fact that maybe the environmental sustainability has not been emphasized enough in engineering courses.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance that engineering has for society in all its aspects (ref), the teaching of this career has been gaining prominence in academic research and discussion forums for educators. Many aspects are discussed, highlighting the sustainability which can greatly contribute to the training of better prepared professionals (Rampasso et al, 2018b). In this context, the present literature review seeks to present the results of some researches that contributes to the debate on the subject.…”
Section: Sustainability Insertion Into Engineering Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…For project management the definition of sustainability and their understanding of aspects of sustainability are important. Rampasso et al (2019) found that according to the learners' perception, the reason for the eliminations of Concern With Employees (CWE); Support for Local Communities (SLC); is related to their perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few examples in the literature about sustainability insertion in engineering courses. Focusing on Brazilian reality, the action research reported by Rampasso, Anholon, Silva, Cooper Ordóñez, et al (2019) should be highlighted. In this study, sustainability aspects related to operations management are presented to mechanical engineering students of a Brazilian university.…”
Section: Sustainability Insertion In Higher Educationmentioning
confidence: 99%